Pengaruh Kepemimpinan Transformasional, Kerjasama Tim dan Integritas Terhadap Penerapan Total Quality Management pada Sekolah Menengah Pertama Katolik di Kabupaten Merauke - Agustinus Arbol; Mimi Salmawati (Universitas Kristen Satya Wacana, 2024)
This study aims to analyze the influence of transformational leadership style, teamwork, and integrity on the implementation of Total Quality Management (TQM) in Catholic Junior High Schools in Merauke. The motivation for this research stems from two primary factors: first, inconsistencies in previous research findings on the impact of transformational leadership, teamwork, and integrity on TQM; second, observable issues such as a lack of integrity among teachers and Foundation employees, poor teamwork, and weak leadership among principals and Foundation administrators, which have resulted in Catholic schools under the Catholic School Education Foundation (YPPK) in Merauke not meeting accreditation standards. TQM is recognized as a strategic approach to enhancing educational quality, fostering an organizational culture committed to continuous improvement and customer satisfaction. his explanatory quantitative research utilized survey methods, gathering data from 100 teachers and educational staff at Catholic Junior High Schools in Merauke. The collected data were tabulated and analyzed using the Statistical Package for the Social Sciences (SPSS) for multiple regression analysis. The results indicate that transformational leadership style, teamwork, and integrity each have a significant positive effect on TQM when considered individually. Additionally, there is a significant combined effect of these factors on the implementation of TQM in Catholic Junior High Schools in Merauke.